Jesus through medieval eyes : beholding Christ with the artists, mystics, and theologians of the Middle Ages - Hamman, Grace (Grand Rapids, MI. Zondervan Reflective, 2023)
"By exploring surprising medieval representations of Jesus in art and literature, Jesus Through Medieval Eyes, by Grace Hamman, expands readers' Christian imaginations. Meeting Jesus as a Knight, a Lover, a Judge, even a Mother allows us to see Christ's face with eyes paradoxically both fresh and ancient, and reorient ourselves towards the Savior"--
"C.S. Lewis noted that the church has a problem: Whenever Christians are brainstorming together about who Jesus is and who we are, we go out and read mostly people who agree with us, or who live in our same time and place. It's hard to separate the cultural wheat from the chaff. But what happens when we do read people's answers to Jesus's question from the past lives and places of the church--people who may be wholly unlike us? Who is Jesus? What is he like? And who am I, encountering Jesus? The answers will surprise you. Jesus Through Medieval Eyes, by Grace Hamman, looks to the Christians of the Middle Ages, to a time and culture dissimilar to our own, for their answers to these questions. Medieval Europeans were also suffering through pandemics, dealing with political and ecclesial corruption and instability, and reckoning with gender, money, and power. Yet their concerns and imaginations are unlike ours. Their ideas, narratives, and art about Jesus open up paradoxically fresh and ancient ways to approach and adore Christ--and reveal where our own cultural ideals about the Messiah fall short.In thoughtful and accessible chapters, medievalist scholar Grace Hamman explores and meditates upon medieval representations of Jesus in theology and literature. These representations of Jesus span from the familiar, like Jesus as the Judge at the End of Days, or Jesus as the Lover of the Song of Songs, to the more unusual, like Jesus as Our Mother. Through the words of medieval people like Julian of Norwich, St. Bernard of Clairvaux, Margery Kempe, and St. Thomas Aquinas, we meet these faces of Jesus and find renewed ways to love the Savior, in the words of St. Augustine, that "beauty so ancient and so new.""--
Keywords: Jesus Christ -- History of doctrines -- Middle Ages, 600-1500.; Jesus Christ -- Iconography; Art, Medieval; Literature, Medieval; RELIGION / Christianity / Literature & the Arts; RELIGION / Christian Living / Personal Growth